The ice flux to the Lambert Glacier and Amery Ice Shelf along the Chinese inland traverse and implications for mass balance of the drainage basins, East Antarctica - Cui, Xiangbin; Du, Wenjia; Xie, Huan; Sun, Bo (Polar Research, 2020)
Study of the mass balance of the Antarctic Ice Sheet is critical to estimate its potential contribution to global sea-level rise in the future. As the largest drainage system, the Lambert Glacier–Amery Ice Shelf drainage system plays an important role in the mass balance of the Antarctic Ice Sheet. In this study, the ice thickness measured by airborne ice-penetrating radar with high spatial resolution and accuracy and accurate ice velocity measured by in situ GPS stations along the route of the Chinese National Antarctic Research Expedition inland traverse were used to calculate the ice flux with unprecedented accuracy. This transverse is from Zhongshan Station to Dome A, passing through the east side of the Lambert Glacier and the smaller coastal glacier in the C-Cp basin. The results show that the ice flux across the entire traverse is 24.7 ± 2.8 Gt a−1, along which the section in drainage basin B–C (Lambert Glacier) has an ice flux of 20.9 ± 1.9 Gt a−1 and the section in drainage basin C–Cp (basin adjacent to Lambert Glacier) contributed 3.8 ± 0.4 Gt a−1. The ice flux values in both regions are coincident with the mass balance calculated from the Ice, Cloud, and Land Elevation Satellite, Earth Observing System. Meanwhile, the C–Cp basin shows an ice flux value of 6.6 ± 0.8 Gt a−1 across the grounding line.
Keywords: Antarktis; havnivåstigning; innlandsis; klimaendringer; målinger

Necessary Conditions for Warm Inflow Toward the Filchner Ice Shelf, Weddell Sea - Daae, Kjersti; Hattermann, Tore; Darelius, Elin Maria K; Mueller, Rachael D; Naughten, Kaitlin A; Timmermann, Ralph; Hellmer, Hartmut H (Geophysical Research Letters, 2020)
Understanding changes in Antarctic ice shelf basal melting is a major challenge for predicting future sea level. Currently, warm Circumpolar Deep Water surrounding Antarctica has limited access to the Weddell Sea continental shelf; consequently, melt rates at Filchner-Ronne Ice Shelf are low. However, large-scale model projections suggest that changes to the Antarctic Slope Front and the coastal circulation may enhance warm inflows within this century. We use a regional high-resolution ice shelf cavity and ocean circulation model to explore forcing changes that may trigger this regime shift. Our results suggest two necessary conditions for supporting a sustained warm inflow into the Filchner Ice Shelf cavity: (i) an extreme relaxation of the Antarctic Slope Front density gradient and (ii) substantial freshening of the dense shelf water. We also find that the on-shelf transport over the western Weddell Sea shelf is sensitive to the Filchner Trough overflow characteristics.
Keywords: Sørishavet; Weddellhavet; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Atmospheric and Oceanographic Signatures in the Ice Shelf Channel Morphology of Roi Baudouin Ice Shelf, East Antarctica, Inferred From Radar Data - Drews, Reinhard; Schannwell, Clemens; Ehlers, Todd A; Gladstone, Rupert; Pattyn, Frank; Matsuoka, Kenichi (Journal of Geophysical Research: Earth Surface, 2020)
Ice shelves around Antarctica can provide back stress for outlet glaciers and control ice sheet mass loss. They often contain narrow bands of thin ice termed ice shelf channels. Ice shelf channel morphology can be interpreted through surface depressions and exhibits junctions and deflections from flowlines. Using ice flow modeling and radar, we investigate ice shelf channels in the Roi Baudouin Ice Shelf. These are aligned obliquely to the prevailing easterly winds. In the shallow radar stratigraphy, syncline and anticline stacks occur beneath the upwind and downwind side, respectively. The structures are horizontally and vertically coherent, except near an ice shelf channel junction where patterns change structurally with depth. Deeper layers truncate near basal incisions. Using ice flow modeling, we show that the stratigraphy is ∼9 times more sensitive to atmospheric variability than to oceanic variability. This is due to the continual adjustment toward flotation. We propose that syncline-anticline pairs in the shallow stratigraphy are caused by preferential snow deposition on the windward side and wind erosion at the downwind side. This drives downwind deflection of ice shelf channels of several meters per year. The depth variable structures indicate formation of an ice shelf channel junction by basal melting. We conclude that many ice shelf channels are seeded at the grounding line. Their morphology farther seaward is shaped on different length scales by ice dynamics, the ocean, and the atmosphere. These processes act on finer (subkilometer) scales than are captured by most ice, atmosphere, and ocean models, yet the dynamics of ice shelf channels may have broader implications for ice shelf stability.
Keywords: Sørishavet; brehylle; geofysikk; glasiologi; innlandsis; isbrem; isshelf

Coherent Seasonal Acceleration of the Weddell Sea Boundary Current System Driven by Upstream Winds - Le Paih, Nicolas; Hattermann, Tore; Boebel, Olaf; Kanzow, Torsten; Lüpkes, Christof; Rohardt, Gerd; Strass, Volker; Herbette, Steven (Journal of Geophysical Research: Oceans, 2020)
The Weddell Sea is of global importance in the formation of dense bottom waters associated with sea ice formation and ocean-ice sheet interaction occurring on the shelf areas. In this context, the Weddell Sea boundary current system (BCS) presents a major conduit for transporting relatively warm water to the Weddell Sea ice shelves and for exporting some modified form of Wedell Sea deep and bottom waters into the open ocean. This study investigates the downstream evolution of the structure and the seasonality of the BCS along the Weddell Sea continental slope, combining ocean data collected for the past two decades at three study locations. The interannual-mean geostrophic flow, which follows planetary potential vorticity contours, shifts from being surface intensified to bottom intensified along stream. The shift occurs due to the densification of water masses and the decreasing surface stress that occurs westward, toward the Antarctic Peninsula. A coherent along-slope seasonal acceleration of the barotropic flow exists, with maximum speed in austral autumn and minimum speed in austral summer. The barotropic flow significantly contributes to the seasonal variability in bottom velocity along the tip of the Antarctic Peninsula. Our analysis suggests that the winds on the eastern/northeastern side of the gyre determines the seasonal acceleration of the barotropic flow. In turn, they might control the export of Weddell Sea Bottom Water on seasonal time scales. The processes controlling the baroclinic seasonality of the flow need further investigation.
Keywords: Sørishavet; Weddellhavet; batymetri; havstrømmer; innlandsis; kontinentalmargin; oseanografi

Deep glacial troughs and stabilizing ridges unveiled beneath the margins of the Antarctic ice sheet - Morlighem, Mathieu; Rignot, Eric; Binder, Tobias; Blankenship, Donald; Drews, Reinhard; Eagles, Graeme; Eisen, Olaf; Ferraccioli, Fausto; Forsberg, René; Fretwell, Peter; Goel, Vikram; Greenbaum, Jamin S; et al. (Nature Geoscience, 2020)
The Antarctic ice sheet has been losing mass over past decades through the accelerated flow of its glaciers, conditioned by ocean temperature and bed topography. Glaciers retreating along retrograde slopes (that is, the bed elevation drops in the inland direction) are potentially unstable, while subglacial ridges slow down the glacial retreat. Despite major advances in the mapping of subglacial bed topography, significant sectors of Antarctica remain poorly resolved and critical spatial details are missing. Here we present a novel, high-resolution and physically based description of Antarctic bed topography using mass conservation. Our results reveal previously unknown basal features with major implications for glacier response to climate change. For example, glaciers flowing across the Transantarctic Mountains are protected by broad, stabilizing ridges. Conversely, in the marine basin of Wilkes Land, East Antarctica, we find retrograde slopes along Ninnis and Denman glaciers, with stabilizing slopes beneath Moscow University, Totten and Lambert glacier system, despite corrections in bed elevation of up to 1 km for the latter. This transformative description of bed topography redefines the high- and lower-risk sectors for rapid sea level rise from Antarctica; it will also significantly impact model projections of sea level rise from Antarctica in the coming centuries.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer

The glacial geomorphology of western Dronning Maud Land, Antarctica - Newall, Jennifer C H; Dymova, Taisiya; Serra, Elena; Blomdin, Robin; Fredin, Hans Ola; Glasser, Neil F; Suganuma, Yusuke; Harbor, Jonathan M; Stroeven, Arjen P (Journal of Maps, 2020)
Reconstructing the response of present-day ice sheets to past global climate change is important for constraining and refining the numerical models which forecast future contributions of these ice sheets to sea-level change. Mapping landforms is an essential step in reconstructing glacial histories. Here we present a new map of glacial landforms and deposits on nunataks in western Dronning Maud Land, Antarctica. Nunataks are mountains or ridges that currently protrude through the ice sheet and may provide evidence that they have been wholly or partly covered by ice, thus indicating a formerly more extensive (thicker) ice sheet. The map was produced through a combination of mapping from Worldview satellite imagery and ground validation. The sub-metre spatial resolution of the satellite imagery enabled mapping with unprecedented detail. Ten landform categories have been mapped, and the landform distributions provide evidence constraining spatial patterns of a previously thicker ice sheet.
Keywords: Dronning Maud Land; geomorfologi; innlandsis; klimaendringer; nunataker; paleoglasiologi

Detailed Seismic Bathymetry Beneath Ekström Ice Shelf, Antarctica: Implications for Glacial History and Ice-Ocean Interaction - Smith, Emma C; Hattermann, Tore; Kuhn, Gerhard; Gaedicke, Christoph; Berger, Sophie; Drews, Reinhard; Ehlers, Todd A; Franke, Dieter; Gromig, Rapahel; Hofstede, Coen; Lambrecht, Astrid; Läufer, Andreas; et al. (Geophysical Research Letters, 2020)
The shape of ice shelf cavities are a major source of uncertainty in understanding ice-ocean interactions. This limits assessments of the response of the Antarctic ice sheets to climate change. Here we use vibroseis seismic reflection surveys to map the bathymetry beneath the Ekström Ice Shelf, Dronning Maud Land. The new bathymetry reveals an inland-sloping trough, reaching depths of 1,100 m below sea level, near the current grounding line, which we attribute to erosion by palaeo-ice streams. The trough does not cross-cut the outer parts of the continental shelf. Conductivity-temperature-depth profiles within the ice shelf cavity reveal the presence of cold water at shallower depths and tidal mixing at the ice shelf margins. It is unknown if warm water can access the trough. The new bathymetry is thought to be representative of many ice shelves in Dronning Maud Land, which together regulate the ice loss from a substantial area of East Antarctica.
Keywords: Dronning Maud Land; batymetri; brehylle; glasiologi; havnivåstigning; innlandsis; isbrem; issmelting; klimaendringer; kontinentalsokkel; seismologi

Ice front blocking of ocean heat transport to an Antarctic ice shelf - Wåhlin, Anna K; Steiger, Nadine; Darelius, Elin; Assmann, Karen M; Glessmer, Mirjam; Ha, Ho Kyung; Herraiz-Borreguero, Laura; Heuzé, Céline; Jenkins, Adrian; Kim, Tae-Wan; Mazur, Aleksandra K; Sommeria, Joël; et al. (Nature, 2020)
Mass loss from the Antarctic Ice Sheet to the ocean has increased in recent decades, largely because the thinning of its floating ice shelves has allowed the outflow of grounded ice to accelerate. Enhanced basal melting of the ice shelves is thought to be the ultimate driver of change, motivating a recent focus on the processes that control ocean heat transport onto and across the seabed of the Antarctic continental shelf towards the ice. However, the shoreward heat flux typically far exceeds that required to match observed melt rates, suggesting that other critical controls exist. Here we show that the depth-independent (barotropic) component of the heat flow towards an ice shelf is blocked by the marked step shape of the ice front, and that only the depth-varying (baroclinic) component, which is typically much smaller, can enter the sub-ice cavity. Our results arise from direct observations of the Getz Ice Shelf system and laboratory experiments on a rotating platform. A similar blocking of the barotropic component may occur in other areas with comparable ice–bathymetry configurations, which may explain why changes in the density structure of the water column have been found to be a better indicator of basal melt rate variability than the heat transported onto the continental shelf. Representing the step topography of the ice front accurately in models is thus important for simulating ocean heat fluxes and induced melt rates.
Keywords: Antarktis; glasiologi; global oppvarming; innlandsis; issmelting; klimaendringer